Provitamin A Maize Biofortification in Sub-Saharan Africa - Kondwakwenda, Aleck; Sibiya, Julia; Zengeni, Rebeca; Musvosvi, Cousin; Andersson, Meike S. (L' Unita di Ricerca per la Valorizzazione Qualitativa dei Cereali, 2018)
Maize (Zea mays L.) has a great potential of combating food insecurity in sub-Saharan Africa because of its wide production and consumption in this region. However, its role in curbing nutrition insecurity is limited due to lack of key micronutrients such as vitamin A. This negates its capacity to be a suitable solution for both food and nutrition insecurities that have plagued many African countries. This has contributed to high prevalence of “hidden hunger” related conditions in the form of vitamin A deficiencytriggered illnesses among others. About fifteenyears ago, HarvestPlus and partners introduced provitamin A maize biofortificaion in Africa to fightVitamin A deficienc. Provitamin A biofortificaion is a technology of increasing the provitamin A density in maize kernels through conventional breeding and/or biotechnology. The suitability of any given breeding strategy depends on the genetics and heritability of the provitamin A accumulation as a trait. This review (1) summarises the impacts of vitamin A deficiencyin sub-Saharan Africa, pointing out the disparities that exist between rural and urban vitamin A deficiencyprevalence in some of the African countries, (2) describes the genetics and molecular science behind maize provitamin A biofortificaion, (3) narrates the progress made so far in terms of maize cultivars development since the inception of maize biofortificaion in sub-Saharan Africa and (4) lastly, challenges of maize biofortificaion and possible solutions are highlighted